الوصية للوارث في مالزيا: دراسة فقهية تحليلية - Fatimah binti Karim (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The subject of this research is "The Will for Heirs in Malaysia: A Juristic Analytical Study". The research deals with the statement of the will for heirs and its conditions in Islam. It then touches on the meaning of the will for heirs in Malaysia, and it is concerned with the presentation of legal articles concerning the will for heirs in Malaysia and the validity of its application in the Malaysian society. The study shows the effectiveness of judicial rulings in Malaysia's Syariah High Court and the implementation of the procedures at the will trust companies in Malaysia towards the issues of the will for heirs in light of the jurisprudence of inheritance. The researcher adopted the inductive, descriptive, and analytical methods, as well as the field study in data collection. In the inductive and descriptive approaches, the researcher extrapolated the main sources of scientific research, and then clarified the reality of the subject. In the analytical approach, the researcher analyzed legal articles and issues concerning will for heirs in the Syariah High Court and the will trust companies in Malaysia. In order to achieve the study's objectives, the field study involved interviews with judges and muftis in selected states of Malaysia; Selangor, Negeri Sembilan, Malacca, Pahang, Kuala Lumpur and Perak, and responsible officials of will trust companies in Malaysia; Selangor Islamic Religious Council (MAIS), Amanah Raya Berhad, As-Salihin Trustee Berhad, and Wasiyyah Shoppe Berhad. One of the important findings of the research is that the applications of the will for heirs in the Syariah High Court and the will trust companies in Malaysia depend on the consent of other heirs, which are in accordance with the principles of Islamic law and are compatible with Muslim Wills Enactment and Administration of the Religion of Islam Enactment. This study also suggests that the Department of Islamic Development Malaysia (JAKIM) should prepare a paper on will for heirs, so that the National Fatwa Committee of Malaysia and the Fatwa Committee of the States can discuss the paper, make decisions and issue the fatwa concerning the law of will for heirs.